Implementation of Balinese Cultural Values to Increase Guest Satisfaction - Merry Dwika Larasati Zaluchu; I Gede Mudana; I Putu Sudira; Ni Wayan Ardini (Catuspata Press, 2021)
Purpose: The purpose of this research is to find out the extent of the Balinese cultural values implemented to the products and facilities to increase guest satisfaction and the influence of the implementation of Balinese cultural values to products and facilities to increase guest satisfaction in Ayodya Resort Bali, Indonesia. Research methods: Data were collected using distributed questionnaires to the 65 of in-house guests of Ayodya Resort Bali, then analyzed using multiple linear regression analysis. Findings: The Balinese cultural values to products and facilities at Ayodya Resort Bali is well implemented to increase guest satisfaction. The result of multiple regression analysis shows that the implementation of Balinese cultural values to products and facilities simultaneously and partially influences positively to increase guest satisfaction in Ayodya Resort Bali. Implications: This research is expected to be useful as an evaluation and consideration in maintaining and improving the implementation of Balinese cultural values to products and facilities in Ayodya Resort Bali.